The Activity of Influenza and Influenza-like Viruses in Individuals Aged over 14 in the 2015/2016 Influenza Season in Poland - Kowalczyk, D. (Respiratory System Diseases, 2017)
Infections in every epidemic season induced by respiratory viruses, especially by the influenza virus, are the cause of many illnesses and complications which often end in death. The aim of this study was to determine the activity of influenza and influenza-like viruses in individuals aged over of 14 in Poland during the 2015/2016 epidemic season. A total of 5070 specimens taken from patients were analyzed. The presence of the influenza virus was confirmed in 40.2% of cases, among which the subtype A/H1N1/pdm09 (62.6% positive samples) predominated. The analysis of confirmed influenza and influenza-like viruses in individuals divided into four age-groups demonstrate that the highest morbidity was reported for the age ranges: 45–64 (13.1%) and 26–44 (12.6%) years. An increase in the number of influenza type B cases (23.7% positive samples), which was the main cause of morbidity in the age group 15–25 years, was noticeable. Given the epidemiological and virological data, the 2015/2016 season in Poland was characterized by increased activity of the influenza virus compared to the previous season. In the 2015/2016 season, there were more than 3.8 million cases and suspected cases of influenza and influenza-like illness, more than 15,000 hospitalizations, and up to 140 deaths.